Prenatal prediction of neonatal haemodynamic adaptation after maternal hyperoxygenation - Ann McHugh; Colm Breatnach; Neidin Bussmann; Orla Franklin; Afif El-Khuffash; Fionnuala M. Breathnach (BMC, 2020)
Abstract The reactivity of the pulmonary vascular bed to the administration of oxygen is well established in the post-natal circulation. The vasoreactivity demonstrated by the fetal pulmonary artery Doppler waveform in response to maternal hyperoxia has been investigated. We sought to investigate the relationship between the reactivity of the fetal pulmonary arteries to hyperoxia and subsequent neonatal cardiac function in the early newborn period. Methods This explorative study with convenience sampling measured pulsatility index (PI), resistance index (RI), acceleration time (AT), and ejection time (ET) from the fetal distal branch pulmonary artery (PA) at baseline and following maternal hyperoxygenation (MH). Oxygen was administered for 10 min at a rate of 12 L/min via a partial non-rebreather mask. A neonatal functional echocardiogram was performed within the first 24 h of life to assess ejection fraction (EF), left ventricular output (LVO), and neonatal pulmonary artery AT (nPAAT). This study was conducted in the Rotunda Hospital, Dublin, Ireland. Results Forty-six women with a singleton pregnancy greater than or equal to 31 weeks' gestational age were prospectively recruited to the study. The median gestational age was 35 weeks. There was a decrease in fetal PAPI and PARI following MH and an increase in fetal PAAT, leading to an increase in PA AT:ET. Fetuses that responded to hyperoxygenation were more likely to have a higher LVO (135 ± 25 mL/kg/min vs 111 ± 21 mL/kg/min, p < 0.01) and EF (54 ± 9% vs 47 ± 7%,p = 0.03) in the early newborn period than those that did not respond to MH prenatally. These findings were not dependent on left ventricular size or mitral valve (MV) annular diameter but were related to an increased MV inflow. There was no difference in nPAAT. Conclusion These findings indicate a reduction in fetal pulmonary vascular resistance (PVR) and an increase in pulmonary blood flow and left atrial return following MH. The fetal response to hyperoxia reflected an optimal adaptation to postnatal life with rapid reduction in PVR increasing measured cardiac output.